Graphene quantum dot-directed synthesis of ultralatge and flexible nanosheets - Zhu, Mengfan (2018)
The size, composition and morphology of materials are critical factors in determining their functions and potential applications. Thus, developing a novel and controllable strategy for synthesis of nanostructure is the key point in material science. Graphene quantum dots (GQDs) and noble metals have drawn enormous attention due to their unique and exceptional physiochemical properties. Herein, we developed a valid strategy for the synthesis of ultralarge and flexible noble metal nanosheets, which was established on the self-assembly of GQDs and noble metal particles in facile aqueous solution followed by a freezed-drying process. Such micro-sized two-dimensional sheet is consisted of ultrasmall nanoparticles, whose size can be easily adjusted by readily tuning the ratio of GQDs and metal amount. In this thesis, a series of Pt-GQDs (PG) and Au-GQDs nanosheets has been synthesized successfully. Additionally, the PG with Pt/GQDs ratio of 10:1.4 was used as electrocatalysts for HER. It exhibited high stability and efficient HER performance (71.7 mV for 100 mA cm-1) comparable to commercial Pt/C catalysts (71.4 mV for 100 mA cm-1). This strategy may provide insights into constructing super nanomaterials for a wide range of applications.